DINOPROSTONE AND MISOPROSTOL FOR INDUCTION OF LABOUR AT TERM PREGNANCY: Dinoprostone And Misoprostol for Induction of Labour - Iftikhar, Bushra; Baqai, Shehla M (Pakistan Armed Forces Medical Journal, 2016)
Objective: Objective of this study is to compare the safety and the efficacy of Prostaglandin E1 (Misoprostol) with Prostaglandin E2 (Dinoprostone). Study Design: Quasi experimental Place and Duration of Study: Department of Obstetrics and Gynecology, PNS SHIFA, Karachi from 22nd March 2006 to 22nd September 2006. Material and Methods: Sixty patients in whom labour induction was indicated were included in the study. They were divided into group A and group B containing 30 patients each. Group A received 50microg of Misoprostol with maximum of 4 doses while group B received Prostaglandin E2 maximum of 2doses. They were primi or second gravida having singleton pregnancy with vertex presentation and Bishop Score less than 4. Results: The results showed that misoprostol group has significant reduction in time for induction and duration of labor as compared to dinoprostone. In misoprostol group more women delivered after single dose compared to dinoprostone. More women in misoprostol group delivered vaginally than abdominally with fewer women require oxytocin augmentation. Neonatal outcome in terms of apgar score and admission in neonatal intensive care unit was similar in two groups. Further and randomized control trials with large sample size are required to assess the safety of drug. Conclusion: Misoprostol with proper monitoring and supervision is an effective agent for induction of labour at term. Its cost effectiveness and easy shelf storage proves it to be a better option, especially in a tropical developing country like ours.